The influence of organic additives on the regioselectivity of oxygenation of alkanes with hydrogen peroxide in the presence of TS-1titanium silicalite - Shul'pin, G. B.; Sooknoi, T.; Shul'pina, L. S. (My University, 2008)
Hydrogen peroxide oxidizes n-hexane, n-heptane, and n-octane at 50°C in the presence titanium silicalite TS-1 as a catalyst, forming isomeric mixtures of ketones and alcohols. Admixtures of organic acids, alcohols, benzene, and ethylbenzene sharply change the ratio of position isomers. For example, the normalized ratio is C(4): C(3): C(2) = 0.44: 1.0: 0.47 for n-heptane oxidation in the absence of additives, but it becomes 0.52: 1.0: 1.00 in the presence of benzyl alcohol and the addition of ethylbenzene changes it to 0.16: 1.0: 0.94. © 2008 MAIK Nauka.